Evaluating the Effect of Knowledge, Attitude, and Practice on Self-Management in Type 2 Diabetic Patients on Dialysis. (10th July 2016) - Ghannadi, Shima; Amouzegar, Atieh; Amiri, Parisa; Karbalaeifar, Ronak; Tahmasebinejad, Zhale; Kazempour-Ardebili, Sara
Abstract : Background. Type 2 diabetes is an increasingly common condition with several preventable microvascular complications such as kidney damage. Nephropathy is expensive to manage, especially as hospital dialysis treatment. Improving patients' knowledge, attitude, and practice (KAP) toward their condition can achieve better control, delay complications, and improve their quality of life. This study evaluated the KAP and self-care behaviors of diabetic patients on dialysis and variables that affect it. Methods. This cross-sectional study was conducted at Shahid Beheshti academic hospitals of Tehran, Iran. Face-to-face interviews were held to fill five validated questionnaires: three evaluating KAP, one evaluating self-management, and one evaluating quality of life. Result. 117 diabetic patients on hemodialysis (42 females) with mean (SD) age of68.70 ± 9.26 years were enrolled in the survey. The scores for patient's KAP, self-care, and quality of life were59.90 ± 11.23, 44.27 ± 8.35, 45.06 ± 12.87, 46.21 ± 10.23, and26.85 ± 13.23, respectively. There was significant negative correlation between patients' knowledge and attitude with their glycosylated hemoglobin level and their fasting blood sugar. There was significant correlation between patients' knowledge and practice with their self-care activities. Conclusion. The present study suggests that patients' KAP scores have a practical effect upon self-care behavior. This highlights the needs for effective diabetes education programs in developing countries like Iran.